KUALITAS PELAYANAN SISTEM VALIDASI DATA SEBAGAI PENUNJANG ADMINISTRASI KEPENDUDUKAN PADA PEMERINTAHAN DESA DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Brilian, Bagus (LPPM UNSAP & FISIP UNSAP, 2024)
n up to date and accurate population data base will support the planning of government, development, and correctional activities, thus requiring a population data validation system as a form of updating by improving service quality optimally. The purpose of this study is to determine the extent to which the quality of service of the data validation system as a support for population administration in the village government in Cimalaka District, Sumedang Regency can be achieved and what are the inhibiting factors and efforts to improve the quality of these services. This research uses qualitative methods with descriptive analysis. Informants were determined using purposive sampling technique. With research informants, namely the general service section of Cimalaka Subdistrict, general service heads of licin village, nyalindung village, cibereum kulon village, and community leaders in the three villages. The data collection techniques used were observation, interview, documentation, and triangulation. While the data processing procedure in this study uses data reduction, data display, data conclution drawing/verification.Based on the results of the study, it is concluded that the quality of service of the validation system in Cimalaka District, Sumedang Regency can be said to be quite good, but there are still factors inhibiting the quality of service, namely there is no special socialization program because it is related to the budget, in terms of service facilities, namely slow internet networks and poor server conditions, and low work standards to achieve data updating targets. There are efforts to overcome obstacles, namely the need to design and prepare the amount of costs incurred to create a special socialization program, the need to increase the accuracy of internet access from 20 mbps to 100 mbps and increase server hosting capacity to minimize errors The suggestions in this study include budgeting to improve supporting facilities and facilities, making information boards related to service requirements and procedures, need to increase public awareness of the importance of one NIK one name personal identification data.